Direct access from general practice to transvaginal ultrasound for early detection of ovarian cancer: a feasibility study - Ladegaard Baun, Marie-Louise; Dueholm, Margit; Heje, Hanne Nørgaard; Hamilton, William; Petersen, Lone Kjeld; Vedsted, Peter (Scandinavian journal of primary health care, 2021)
To investigate the feasibility of providing general practitioners (GPs) direct and fast referral access to transvaginal ultrasound (TVUS). A prospective cohort study. A total of 232 Danish general practices in parts of the Central Denmark Region. Women aged ≥40 years who consulted their GP for vague and non-specific symptoms (n = 479). The feasibility assessment included the GPs' referral rate, indications for referral, management of test results, and findings from TVUS. A total of 479 women were referred to TVUS. The examinations revealed abnormalities in 104 (21.7%) women. Additional investigations were needed in 68 (14.2%) women of whom seven (1.5%) underwent major surgery. No case of ovarian cancer was diagnosed during the study period or the 6-month follow-up. However, three (0.6%) women with an abnormal transvaginal ultrasound were diagnosed with urogynecological cancer; this yielded a PPV of 4.4% (95% confidence interval: 1.5-12.2) and an NPV of 100.0% (95% confidence interval: 96.7-100.0) for urogynecological cancer. Providing GPs with direct access to transvaginal ultrasound was feasible; 80% of the investigated women were referred back to the GP, 14% were further investigated, 0.6% were diagnosed with urogynecological cancer, and 1.5% had major procedures performed without complications. Direct access to TVUS could be an important pathway to ensure fast evaluation of women presenting with vague non-specific symptoms of potential ovarian cancer. Future studies should explore the patient experience, cancer outcomes, and health economics issues. KEY POINTS Current awareness  * GPs have no fast referral option for women presenting with vague non-specific symptoms that could indicate underlying ovarian cancer.   Key findings  * We offered GPs direct and fast referral access to TVUS; 51.7% of practices used the opportunity.  * The GPs referred 479 women to TVUS; 104 had an abnormal TVUS and 68 needed additional investigations.  * Seven women underwent major surgery, leading to three cases of urogynecological cancer. No woman had a false negative TVUS result.